What's Left of the Left : Democrats and Social Democrats in Challenging Times - Shoch, James; Ross, George, 1940-; Cronin, James E. (Book collections on Project MUSE., 2011)
What's Left of the Left offers studies comparing how center-left political parties and movements have fared since the 1970s throughout Europe and in the United States.